Pengaruh Kegel Exercise terhadap Inkontinensia Urine pada Ibu Postpartum Multipara - Murti Sari Ningsih; Erika Erika; Rismadefi Woferst (Holistic Nursing and Health Science, 2021)
Introduction: One of problems experienced post-partum mothers is urine incontinence. Kegel exercise effects on urine incontinence post-partum mothers and elderly. However, limited study search for its effect on multiparous post-partum mothers. This study aims to determine the effect of Kegel exercise on urinary incontinence in multiparous post-partum mothers.Methods: The research design used was a quasi-experiment with a post-test with control group design which was divided into an experimental group and a control group. The research was conducted in the work area of Rejosari Public Health Center with a sample size of 34 respondents with the criteria of multiparous postpartum mothers who experienced urinary incontinence in normal labor with a purposive sampling technique. The measuring instrument used was the International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF). Data analysis used dependent and independent t-test.Results: The results of the dependent t-test statistic with α 0.05 showed that Kegel exercise was effective against urinary incontinence in the experimental group p value (0.000) and the control group p value (0.033) and the results of the independent t-test showed that there was an effect of Kegel exercise on urinary incontinence in the experimental group and the control group p value (0.004). The results of this study can be used as a reference for using Kegel exercises as a way to deal with complaints of urinary incontinence in multiparous post-partum mothers.